ممارسة حرفتي الرعي و تربية الماشية في نوميديا من خلال نصوص النقيشات اللاتينية . - بوشارب, سلوى (University of Eloued جامعة الوادي, 2021)
يتناول موضوع ممارسة حرفتي الرعي وتربية الماشية في مقاطعة نوميديا من خلال نصوص النقيشات اللاتينية الاجابة على اشكالية رئيسة تتمحور حول طبيعة المهن أو الحرف المتعلقة بممارسة النشاط الرعوي (الرعي و تربية الحيوانات) وعلاقتها بفئات معينة في المجتمع النوميدي و كذا بطبيعة المنطقة من الناحية الجغرافية بهدف الكشف عن الواقع الاقتصادي للطبقات الدنيا في المجتمع النوميدي مع اعادة الاعتبار لأصحاب الحرف و المهن البسيطة ذات الفعالية في المجال الاقتصادي. Abstract: The subject of the practice of pastoral activity (herding and raising livestock) in the province of Numidia, through the texts of Latin inscriptions, addresses a major problem centered on the nature of the professions or crafts related to the practice of pastoral activity (herding and animal husbandry) and their relationship to certain groups in the Numidian society, as well as the nature of the region in terms of Geographical in order to reveal the economic reality of the lower classes in the Numidian society with the restoration of consideration for the owners of crafts and simple professions that are effective in the economic field.
مقال